Chemical characteristics and thickness of Podocnemis expansa post-hatching eggshells (Testudines, Podocnemididae) - Caio Henrique Ferreira; Lucélia Gonçalves Vieira; Sady Alexis Chavauty Valdes; Juliana dos Santos Mendonça; Evandro de Abreu Fernandes; André Luiz Quagliatto Santos (Acta Scientiarum: Biological Sciences, 2016)
Knowledge on chemical components of the post-hatching eggshell of reptiles may provide indicators of the quality of the diet offered to females kept in captivity. Therefore, the objective of this study was to investigate the chemical characteristics of the calcareous layer, as well as the thickness of Podocnemis expansa post-hatching eggshells. Eggshell thickness was 183±1.405 µm. This value is similar to that of the eggs of other Testudines with flexible eggshells. As for the chemical composition, the following percentages were observed: nitrogen 7.983 ± 0.054; crude protein 49.91 ± 0.324; crude fat 0.068 ± 0.002; mineral matter 20.302 ± 0.807; calcium 13.374 ± 0.647; and phosphorus 0.176 ± 0.003. Knowledge on chemical composition of the eggshell may aid the nutrition of P. expansa raised in commercial facilities, once this species is an alternative and promising source of exotic meat.